PERSONAL ENVIRONMENT AND STRESS AMONG BANK EMPLOYEES IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Stress Management is getting increasingly more consideration now-a-days, especially in the financial sector. There is no work in this world without stress. Everybody in their work is presented to pressure also, nervousness as they traverses the obligations doled out to them. Banking industry which is the foundation of the country’s economy is not an outstanding one. The activity idea of banking workers is dreary as it includes the immediate client communication in all levels. So the researchers take an attempt to study the family factors which creates stress among the bank employees during their work. This study focuses in Kanyakumari District. The lower and middle level bank employees are chosen for the study. This study was intended to test and investigate observationally the family related reason for stress among bank employees.